Sputum colour variability and clinical outcomes in bronchiectasis: a multicentre Canadian-UK study - Christina S. Thornton; Louise Jackson; Chanhee Seo; Jo Fothergill; David Green; Dan Mccauley; Phil Mitchelmore; Kamlesh Mohan; Dilip Nazareth; Michael D. Parkins; Harvey R. Rabin; Dennis Wat; et al. (ERJ Open Research, 2026)
Background Sputum colour is a marker of neutrophilic airway inflammation and correlates with disease severity in European bronchiectasis cohorts, but its longitudinal behaviour and clinical significance remain unclear. In this study, we sought to examine sputum colour in Canadian and UK cohorts to assess its stability over time and relationship to disease severity and activity. Methods Adults with non-CF bronchiectasis in the Calgary Biobank (CAN) and Liverpool POSTED (UK) cohorts were prospectively followed for up to 20 years. Sputum colour was assessed using the investigator-rated Murray 4-point chart (both cohorts) and patient-reported BEST score (UK only). Clinical features and outcomes were compared across sputum-colour scores and variability subgroups, and changes in Murray and BEST scores were analysed in relation to outcomes. Results Across 1193 samples from 86 patients, purulent sputum correlated with lower lung function, higher BSI scores, more exacerbations, and higher prevalence of chronic P. aeruginosa . Sputum colour was stable in ∼90% of samples, but patients with variable colour had more severe disease than those with persistently mucoid sputum. Investigator–patient discordance was common. Objective colour changes did not predict time to next exacerbation (TTNE), whereas patient-reported colour change and BEST score shifts were associated with shorter TTNE and greater antibiotic use. Conclusions This international study shows sputum colour is a prognostic biomarker with defined short- and long-term stability. Murray colour variability helps stratify disease severity, while patient-reported and BEST score changes, despite frequent discordance with investigator ratings, are more strongly associated with short-term clinical deterioration and antibiotic use.